Managing the visual environment of a fashion store: Effects of visual complexity and order on sensation-seeking consumers. Issue 2 (3rd January 2018) - Jang, Ju Yeun; Baek, Eunsoo; Choo, Ho Jung
Abstract : Purpose: The purpose of this paper is to investigate the effect of a fashion store's visual complexity on consumers' behaviour. Considering environmental order and individuals' sensation-seeking tendencies, the authors examine the effect of visually complex fashion stores on consumers in a more conclusive way to address the inconsistent effect found in the previous literature. Design/methodology/approach: This study features a 3 (visual complexity level: low, medium, high) × 2 (environmental order condition: low, high) between subjects design, with individual sensation-seeking tendency included as a moderator. Using this design, an online survey was administered to 188 participants in South Korea. Findings: The results indicate that there is a three-way interaction, where the interaction effect of visual complexity and environmental order is moderated by individuals' sensation-seeking tendency. The effect of visual complexity on approach behaviours had an inverted U-shape in the low-order condition, while had a positive linear shape in the high-order condition, and the interaction effect was significant only for high-sensation seekers. Practical implications: The findings assist practitioners in establishing strategies for visual merchandising and store design within fashion stores. It is suggested that retailers consider environmental order when organising a large amount of varied merchandise in a complex environment. Store managers must adjust the complexity and environmental order to meet the optimal stimulation level of their target consumers. Originality/value: This study strengthens the literature on visual complexity by applying the concept to the retail environment. The results provide a significant contribution to the literature because they show how individual-level and store-level variables interact to influence consumer behaviour.